1998
DOI: 10.1104/pp.118.1.37
|View full text |Cite
|
Sign up to set email alerts
|

The Two Genes Encoding Starch-Branching Enzymes IIa and IIb Are Differentially Expressed in Barley1

Abstract: The sbeIIa and sbeIIb genes, encoding starch-branching enzyme (SBE) IIa and SBEIIb in barley (Hordeum vulgare L.), have been isolated. The 5 portions of the two genes are strongly divergent, primarily due to the 2064-nucleotide-long intron 2 in sbeIIb. The sequence of this intron shows that it contains a retro-transposonlike element. Expression of sbeIIb but not sbeIIa was found to be endosperm specific. The temporal expression patterns for sbeIIa and sbeIIb were similar and peaked around 12 d after pollinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 51 publications
10
100
0
Order By: Relevance
“…7). As reported earlier (Sun et al, 1998;Burton et al, 1999;Radchuk et al, 2009), the transcripts of HvSBEIIb and HvLD were mainly found in the endosperm and are thus likely to be involved in the biosynthesis of storage starch (Table I; Fig. 8).…”
Section: Diurnal Regulation Of Starch Metabolism and Sugar Signalingmentioning
confidence: 56%
“…7). As reported earlier (Sun et al, 1998;Burton et al, 1999;Radchuk et al, 2009), the transcripts of HvSBEIIb and HvLD were mainly found in the endosperm and are thus likely to be involved in the biosynthesis of storage starch (Table I; Fig. 8).…”
Section: Diurnal Regulation Of Starch Metabolism and Sugar Signalingmentioning
confidence: 56%
“…1). This is similar to the situation in barley and might reflect a differential partitioning of the SBEIIA and SBEIIB isoforms (Sun et al, 1998).…”
Section: Sequence Analysis Of Sorghum Sbeiiamentioning
confidence: 59%
“…(2003) using 32 P-labelled gene-specific cDNA fragment for sorghum SBEI and SBEIIB , sorghum SBEIIA (this work) and barley SBEIIB (Sun et al, 1998). The membranes were striped of the radioactive probes in a boiling 0.5% (w/v) SDS solution and re-hybridized with 18S rRNA-labeled probes.…”
Section: Dna and Rna Blot Analysesmentioning
confidence: 99%
“…SBE-IIb plays a specific role in the formation of Achains of the amylopectin cluster (Nishi et al 2001), and the levels of BEIIb activity affect the extent of structural changes in the cluster (Tanaka et al 2004). In monocots, SBE-II is made up of two closely related but discrete gene products (SBE-IIa and SBE-IIb) (Sun et al 1998;Rahman et al 2001;McCue et al 2002). Downregulation of SBE-I activity appears to have minimal effects on starch syntheses and composition in photosynthetic and non photosynthetic tissues (Satoh et al 2003).…”
Section: Sbe Genesmentioning
confidence: 99%